Metodologia para avaliação da tribocorrosão durante o ensaio intermitente do aço super duplex UNS S32750 nitretado por plasma em baixa temperatura - Tecchio, Denise (2022)
Low temperature plasma nitriding treatment has been widely studied as an alternative to increase surface hardness and wear resistance, without impairing the corrosion resistance of stainless steels. To evaluate the performance of these materials, tribocorrosion studies that evaluate the simultaneous action of electrochemical and mechanical effects in a tribological contact are increasingly common. Tribocorrosion tests are generally classified as continuous, where the metal is continuously exposed to an aggressive medium, and intermittent tests, which allow the repassivation of the material. However, in intermittent tests, there is a difficulty in quantifying the portions of loss due to corrosion and wear and the UNE 112086 standard suggests that this quantification is based on electrochemical results measured in continuous tests. Thus, there is a need to improve existing methodologies to enable the use of electrochemical techniques in intermittent testing. In this context, the objective of this work was to investigate the application of electrochemical techniques in the evaluation of tribocorrosion during the intermittent test of UNS S32750 super duplex steel without treatment and plasma nitrided at a temperature of 400 °C for 4 hours. To this end, reciprocal slip tests were performed in 0.5M NaCl solution under electrochemical monitoring using linear polarization resistance (RPL) and open circuit potential (PCA) techniques. In addition to the intermittent slip condition, the continuous slip condition was also used to evaluate the methodology. After nitriding treatment, the samples were characterized by the following analysis techniques: X-ray Diffraction (XRD), Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Vickers Microhardness and Nanoindentation. The results indicate the formation of nitrided layers rich in γN phase with an average thickness between phases of 9.7 μm and an average microhardness of 1300 HV0.025. The proposed methodology to assess tribocorrosion is based on the UNE 112086 (2016) standard. It can be concluded that the methodology adopted can be used to evaluate the resistance to tribocorrosion of untreated and plasma nitrided UNS S32750 steel. From the RPL measurements during the intermittent test, it was possible to measure material losses due to corrosion of the active and repassivated areas. Tribocorrosion results indicate a significant reduction in volume loss for the nitrided condition compared to the untreated condition regardless of the slip condition.